2016
DOI: 10.1515/intag-2015-0084
|View full text |Cite
|
Sign up to set email alerts
|

Effect of composition on physical properties of food powders

Abstract: A b s t r a c t . The paper presents an influence of raw material composition and technological process applied on selected physical properties of food powders. Powdered multi-component nutrients were subjected to the process of mixing, agglomeration, coating, and drying. Wetting liquids ie water and a 15% water lactose solution, were used in agglomeration and coating. The analyzed food powders were characterized by differentiated physical properties, including especially: particle size, bulk density, wettabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…The powders with silica were characterized by very good or good flowability, because HR100, HR500, and HR1250 values ranged from 1.08 to 1.30. The effect of reducing flowability of material along with an increasing degree of bed packing in fine powders obtained in this study was consistent with findings of other authors (Domian and Cenkier 2013, Domian et al 2014, Samborska et al 2015, Szulc and Lenart 2016. Drusch et al (2006) applied various flowability-improving preparations in powders of fish oil and determined their optimal addition at the level of 1%.…”
Section: Resultssupporting
confidence: 91%
“…The powders with silica were characterized by very good or good flowability, because HR100, HR500, and HR1250 values ranged from 1.08 to 1.30. The effect of reducing flowability of material along with an increasing degree of bed packing in fine powders obtained in this study was consistent with findings of other authors (Domian and Cenkier 2013, Domian et al 2014, Samborska et al 2015, Szulc and Lenart 2016. Drusch et al (2006) applied various flowability-improving preparations in powders of fish oil and determined their optimal addition at the level of 1%.…”
Section: Resultssupporting
confidence: 91%
“…Water‐ and oil‐binding capacities were determined as per the method of Guan et al . (2007), wettability as per the method of Szulc & Lenart (2016) and dispersibility as per the method of Saha et al . (2019).…”
Section: Methodsmentioning
confidence: 99%
“…Foaming capacity (FC) was determined as per the method mentioned by Fekria et al (2012) and expressed as the per cent volume increased after stirring. Water-and oil-binding capacities were determined as per the method of Guan et al (2007), wettability as per the method of Szulc & Lenart (2016) and dispersibility as per the method of Saha et al (2019).…”
Section: Functional Characterisationmentioning
confidence: 99%
“…For H. sabdariffa powders, no clear influence of mean particle size could be drawn from ff values, but it appeared that flowability was maximized for granulometric classes of intermediate size (212-315 lm). This may arise from the combination of the deleterious influence of shape irregularity of large particles and the higher cohesion of small particles (due to the higher number of contact points between small particles (Nan et al, 2017;Szulc and Lenart, 2016). The latter phenomenon has been evidenced by Fitzpatrick et al (2005) for corn starch powder, cocoa powder, wheat flour and soy flour, who showed that powders with smaller particle size tend to have a smaller flow index.…”
Section: Flowability In High-stress Conditionsmentioning
confidence: 99%
“…Studies have been conducted to understand the influence of particle size on powder physical and flow properties (Maeda et al, 2017;Siliveru et al, 2017). However, conclusions were rather different depending on the intrinsic properties of plant materials such as surface properties (Petit et al, 2017;Szulc and Lenart, 2016), granulometric and shape properties of produced powder (mean particle size, with of particle size distribution, shape and surface roughness) and process conditions employed during powder production (Kim et al, 2009). For instance, Singh and Prasad (2013) reported an increase in aerated bulk density with particle size for Moringa oleifera leaf powders, while Sharma et al (2013) observed an opposite trend for mango pulp powders.…”
Section: Introductionmentioning
confidence: 99%